2014
DOI: 10.1128/aem.02616-13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Escherichia coli on Flies at Poultry Farms

Abstract: In the Netherlands, extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli bacteria are highly prevalent in poultry, and chicken meat has been implicated as a source of ESBL-producing E. coli present in the human population. The current study describes the isolation of ESBL-producing E. coli from house flies and blow flies caught at two poultry farms, offering a potential alternative route of transmission of ESBL-producing E. coli from poultry to humans. Overall, 87 flies were analyzed in 19 pools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 38 publications
1
93
1
3
Order By: Relevance
“…Studies showed that ESBLs-producing enterobacteria are multidrug resistant (Guandong and Avci, 2013;Blaak et al, 2014). Therefore, the multidrug resistance observed in this study may be as a result of ESBLs that the isolates might have produced (Blaak et al, 2014). The high multidrug resistance exhibited among enterobacterial isolates in this study, portends adverse impact on the food chain in the study area.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Studies showed that ESBLs-producing enterobacteria are multidrug resistant (Guandong and Avci, 2013;Blaak et al, 2014). Therefore, the multidrug resistance observed in this study may be as a result of ESBLs that the isolates might have produced (Blaak et al, 2014). The high multidrug resistance exhibited among enterobacterial isolates in this study, portends adverse impact on the food chain in the study area.…”
Section: Discussionmentioning
confidence: 74%
“…Adenaike et al (2013) reported 89% multidrug resistance among ESBL-resistant E. coli isolates from roasted beef in Northern Nigeria. Studies showed that ESBLs-producing enterobacteria are multidrug resistant (Guandong and Avci, 2013;Blaak et al, 2014). Therefore, the multidrug resistance observed in this study may be as a result of ESBLs that the isolates might have produced (Blaak et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…It is well known that ESBL-resistant enterobacteria are common cause of community and hospital-associated infections in humans and companion animals (Sun et al, 2010;Rubin and Pitout, 2014). These infections are often fatal due to limited therapeutic options, resorting to the use of carbapenems is usually the treatment option (Dierikx et al, 2012;Blaak et al, 2014). This has resulted in increasing numbers of isolation of carbapenem-resistant organisms (superbugs) from humans and animals, including companion animals, worldwide (Shaheen et al, 2013;Guerra et al, 2014;Yousfi et al, 2015).…”
Section: Isolation and Generic Identification Of Esbl-resistant Entermentioning
confidence: 99%